Metode Analisis Keuangan Untuk Pengoperasian Aplikasi Buku Warung - Anike Putri; Ghea Nofayza; Widi Dwi Aditia Putra; Delia Arofah (Jurnal Bhakti Karya dan Inovatif, 2023)
For MSMEs, several steps can be taken in order to manage finances well, namely starting to separate personal and business finances, and starting simple bookkeeping. If MSMEs are able to separate personal finance from business finance, and have bookkeeping or administrative management (business finance), MSMEs can try to make financial planning in a simple way. By separating personal and business financial records, owners can more easily manage their business finances. This is because the accuracy of business financial records can influence decision making and evaluate business performance. Mixed cash flow between personal and business finances can make it difficult for MSME actors to determine business operating costs. One strategy for separating personal and business financial records is that the owner can "pay" himself so that all personal needs are recorded from the salary post.Keeping daily financial records is a simple thing, but can bring great benefits in the long term. Companies with complete and accurate financial records will have advantages in terms of evaluation and monitoring. The development of internet technology and applications must be utilized by MSME business people. However, business actors must also be able to determine exactly what applications will be used to support the overall operation of their business. As technology develops, MSME players can take advantage of digital applications to help manage their business more effectively. By utilizing digital applications, MSMEs can find out financial transactions more quickly and accurately. The specific target in this community service activity is to provide knowledge and training to Shoe Craftsmen of the Cibaduyut Sub-District regarding understanding the basic finances for operating the Buku Warung application.